BRIDGING PUBLIC PERCEPTION: BARRIERS TO ISLAMIC BANKING ADOPTION - Wahidullah, Wahidullah; Jumaiyah, Jumaiyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to assess the current views of the Jepara community towards sharia banking products, as well as the factors that influence these perceptions. This thesis was prepared using descriptive-qualitative research methods. A study of citizens' perceptions shows that sharia banking products are considered easy to use, cost-effective, and convenient. They appreciate the availability of ATM cards and BSI banking facilities for transactions anytime and anywhere. For interbank transfers, the administration fee is cheap—only 2,500. Sharia People's Economic Bank (SPEB) products are not subject to any administration fees or deductions, thus ensuring security, reliability, and compliance with Islamic principles. Factors that influence public perception of sharia banking products include understanding determinants, motivation factors, size factors, and movement factors. These factors have contributed to the perception that people are reluctant to use Islamic banks due to a lack of understanding of banking products. Compliance with Sharia is now very minimal.